Synthesis of α- and β-Rhombohedral Boron Powders via Gas Phase Thermal Dissociation of Boron Trichloride by Hydrogen - Ağaoğulları, Duygu; Balcı, Özge; Duman, İsmaİl; Öveçoğlu, M. Lütfİ (Springer Science and Business Media LLC, 2011)
The α-rhombohedral and β-rhombohedral crystal structures of pure elemental boron powders have been synthesized via gas phase thermal dissociation of BCl3 by H2 on a quartz substrate. The parameters affecting the crystal structures of the final products and the process efficiency, such as BCl3/H2 molar ratio (1/2 and 1/4) and reaction temperature (1173 K to 1373 K [900 °C to 1100 °C]), have been examined. The experimental apparatus of original design has enabled boron powders to be obtained at temperatures lower than those in the literature. The surface/powder separation problem encountered previously with different substrate materials has been avoided. Boron powders have been synthesized with a minimum purity of 99.99 pct after repeated HF leaching. The qualitative analysis of exhaust gases has been conducted using a Fourier transform infrared spectroscope (FTIR). The synthesized powders have been characterized using an X-ray powder diffractometer (XRD) and scanning electron microscope (SEM) techniques. The results of the reactions have been compared with equilibrium predictions performed using the FactSage 6.2 (Center for Research in Computational Thermochemistry, Montreal, Canada) thermochemical software.